Implementation of Restorative Justice in the Criminal Act of Illegal Retail Sale of Petroleum (BBM) (Case Study at the Mojokerto District Attorney's Office) - Almira, Zhafirah Nisa; Suwondo, Denny (Jurnal Hukum Khaira Ummah, 2025)
Legal retail fuel sales are an event that is often encountered in society, but many people do not have permission from the authorities in the activity of buying and selling Pertalite fuel so that people will be subject to the Oil and Gas Law. This thesis aims to study and analyze: First, How is the Implementation of Restorative Justice in the Criminal Act of Illegal Retail Fuel Sales (Case Study at the Mojokerto District Attorney's Office), Second, what are the obstacles and solutions in the Implementation of Restorative Justice in the Criminal Act of Illegal Retail Fuel Sales, Third, how is the implementation of Restorative Justice against the Criminal Act of Illegal Retail Fuel Sales in the future. The approach method used in this study is a sociological legal approach, the research specifications used are descriptive normative, primary and secondary data sources and using qualitative analysis. This writing is analyzed with the theory of justice, restorative justice, and the legal system. Based on the research results, it can be concluded: (1) the application of Restorative Justice in the Criminal Act of Retail Sale and Purchase of Fuel Oil (BBM) at the Mojokerto District Attorney's Office is not only based on normative rules but also considers the level of reprehensibility, social and economic conditions, and losses by prioritizing humanistic law enforcement, (2) the obstacles in the application of RJ for retail sale and purchase of fuel oil are the rules that limit a case that can be RJ, socialization regarding the rules for the sale and purchase of fuel oil has not been implemented widely, there is still subjectivity in determining whether a case can be RJ or not, the solution is to align views and use conscience in implementing restorative justice, conduct socialization regarding the sale and purchase of fuel oil in retail so that there is no more ignorance of the law in society, review regulation 15 of 2020 concerning termination based on restorative justice regarding the requirements for restorative justice, (3) the application of Restorative Justice to the Criminal Act of Illegal Retail Sale and Purchase of Fuel Oil (BBM) in the future, namely the termination of prosecution based on restorative justice in the Attorney General's Office of the Republic of Indonesia is an effort to reform the national legal system which has so far only adhered to the positivist paradigm and as Ultimum remedium which means "last resort" or "last resort".